Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.techsoc.2021.101830
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting attitudes: Analyzing social media data to understand the early discourse on COVID-19 passports

Abstract: In several countries, vaccine passports are being encouraged to hasten the return to some form of normalcy amidst the COVID-19 pandemic. Vaccine passport is a digital or paper document that may serve as proof of the COVID-19 vaccine, thereby allowing entry to public venues, sporting events, air travel, and unrestricted access to other facilities. This study explores how the COVID-19 passport is being discussed and perceived on Twitter and the prominent entities involved in the early discourse on the issue. Twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 43 publications
5
32
1
Order By: Relevance
“…Studies have found a correlation between a favourable attitude towards CVCs and the desire to travel [ 11 , 20 ]. Hence, by including a variable on travel plans in 2021, we hypothesised that people who had no travel plans in 2021 would be more likely to oppose CVCs as they are less likely to have utility and benefit from having it.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have found a correlation between a favourable attitude towards CVCs and the desire to travel [ 11 , 20 ]. Hence, by including a variable on travel plans in 2021, we hypothesised that people who had no travel plans in 2021 would be more likely to oppose CVCs as they are less likely to have utility and benefit from having it.…”
Section: Methodsmentioning
confidence: 99%
“…Both NPIs and CVCs have been viewed as restrictive policies that violate human rights [ 11 ]. Hence, we included a variable on whether existing NPIs (such as social distancing, mask wearing, testing, quarantine) should continue in their own country and hypothesised that people opposing existing NPIs are also more likely to oppose CVCs as they prohibit freedom of movement for the unvaccinated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccine hesitancy is a problem nearly as old as vaccines themselves, and in recent years, scholars from multiple disciplines have taken a new interest in this topic [5] . Pakistan is a notable case with respect to vaccine hesitancy because it remains one of two remaining countries where polio has not been eliminated [6] .…”
Section: Introductionmentioning
confidence: 99%